The strength training anatomy workout - Delavier, Frederic (Human Kinetics, 2011)
Over one million readers have turned to Strength Training Anatomy for strength training's most effective exercises. Now put those exercises to work for you with The Strength Training Anatomy Workout. The Strength Training Anatomy Workout is your guide to creating the body and the results you want. Strengthen arms and legs; increase muscle mass; sculpt chest, back, and core; firm glutes; increase hip flexibility . . . it's all here, and all in the stunning detail that only Frédéric Delavier can provide! Over 150 full-color illustrations allow you to get inside more than 200 exercises and 50 workouts to see how muscles interact with surrounding joints and skeletal structures. You'll also discover how variations, progressions, and sequencing can affect muscle recruitment, the underlying structures, and ultimately the results. The Strength Training Anatomy Workout includes proven programming for strength, power, bodybuilding, and toning that can be used in a gym or at home. You'll find targeted conditioning routines for optimal performance in more than 30 sports, including basketball, football, soccer, track and field, and golf. Former editor in chief of PowerMag in France, author and illustrator Frédéric Delavier is a journalist for Le Monde du Muscle and a contributor to Men's Health Germany and several other strength publications. His previous publication, Strength Training Anatomy, has sold more than one million copies.